Một mô hình cài đặt các giao thức truyền thông trên mạng máy tính - Hải, Nguyễn Thúc (Journal of Computer Science and Cybernetics, 2016)
A model for implementing portable communication protocols is described. This study has been done to make portable network software, concerning in particular OSI standard protocols. This paper shows, first, a methodology and tools for communication protocol implementation under UNIX operating system.